Effectiveness of Smarted B Father Intervention to Reduce a Pregnant Mother’s Anxiety in the Third Trimester - M. Ardan; Zulkifli Umar; Elma Novita Indonesiani; Mayela Rochyati Nggode; Jihan Patrizia (Sean Institute, 2022)
Emotional anxiety often occurs in pregnant mothers 29.2% compared to postpartum mothers 16.5%. Anxiety that occurs during pregnancy can affect between 15-23% and can increase the negative risk for mothers and children born. Indonesia reported that 28.7% experienced anxiety in the third trimester of pregnancy, anxiety during pregnancy can increase before delivery which is manifested as anxiety about having a miscarriage, anxiety about fetal abnormalities, fear of giving birth, and pain during delivery. This study aims to analyze the effectiveness of the Smart Education Based on Family Approach Therapy (SMARTED B FATHER) intervention to reduce a pregnant mother’s anxiety in the third trimester. This study used a quasi-experimental pretest-posttest research design with a control group design which was divided into 2 groups (17 respondents in the intervention group and 17 respondents in the control group). The results of the normality test of the data obtained that the data were normally distributed, so the results of the analysis using paired t-test showed that there was a decrease in anxiety levels before and after the Smarted B Father Intervention in the intervention group (p-value 0.002) and there was no decrease in anxiety levels in the control group (p-value 0.113), while the results of the analysis using an unpaired t-test showed that there was a difference in the level of depression after the Smarted B Father Intervention between the intervention and control groups with a p-value of 0.001. This research can also provide recommendations to health workers, especially midwives to provide services in the form of complementary care services